The Existence of Representational Meaning in Supporting Ideational Meaning in the Radio Communication On Board Texts in MarEng™ Learning Tool - Bedagama, Diana Novietasari; Rukmini, Dwi; Linggar Bharati, Dwi Anggani (English Education Journal, 2021)
English is a lingua franca on the sea; seafarers must communicate using English in radio communication. In facilitating cadets’ meaning-making process of English in radio communication, MarEng™ Learning Tool by Turku University has been used as one of the innovative language learning tools. It is a multimodal learning media which provides verbal texts accompanied by visual text. This study aims to explain how the representational meanings of visual images support the ideational meanings of the verbal texts existed in in MarEng Learning Tool, which are analyzed using Grammar of Visual Design and Systemic Functional Linguistic approaches. The analysis of representational meaning was conducted by concerning the presence of vectors and other visual items realizing representational meaning. Moreover, the ideational meaning analysis was focused on the analysis of the transitivity of the verbal texts. The findings revealed the representational meaning of the images supports the ideational meaning. The existence of representational meaning in MarEng™ Learning Tool was to describe the participants and the situation in the radio communication on board in the texts.